A comparative study of adult and pediatric polysomnography - K., Athiyaman; M., Gowri Shankar; G., Suji; D., Prabhu (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Obstructive sleep apnea (OSA) also referred to as obstructive sleep apnea-hypopnea-is a sleep disorder that involves cessation or significant decrease in airflow in the presence of breathing effort. It is the most common type of sleep-disordered breathing and is characterized by recurrent episodes of upper airway collapse during sleep. Pediatric obstructive sleep apnea syndrome (OSAS), like adult OSAS, is characterized by intermittent upper airway collapse during sleep and is associated with anatomic and neuromuscular factors. However, the clinical manifestations, diagnostic criteria, and polysomnographic findings of OSAS in children are likely to be different from those in adults. Adult OSA and pediatric OSA though the pathogenesis is more or less same, the evaluation gives a significant difference in outcome. Methods: 60 patients who meet the inclusion criteria were subjected to clinical evaluation and level 1 sleep study was done. Results: Mean age group in adults was 39.86±8.42 yrs the most common cause in adults being obesity and the mean age group in pediatric was 7.63±1.71 yrs with adenotonsillar hypertrophy being the commonest cause. The gender distribution among affected is predominantly being male both in adults and in the pediatric population. The lowest mean desaturation was 81% in adults as compared to 73.23% in children. Conclusions: Significant PSG findings were noted in gender distribution and in Mean desaturation, AHI in both adults and pediatric population.